Doubled Embodiment and the Temporal Experience of Illness in Comics (ENTHYMEMA, 2025)
This contribution considers the centrality of pictorial embodiment in autobiographical comics. It begins by tracing pictorial embodiment’s connection to othering and then examines the popular practice of doubled embodiment in graphic illness narrative. Expanding upon theorizations of doubled embodiment as manifesting subjective experiences of illness, several examples will serve to trace how double embodiment in graphic illness narratives speaks to the ill subject’s personal experience of time. Ultimately, this contribution proposes that double embodiment can indicate how, in illness, time intersects with considerations of minds and emotional states. In the works of graphic illness studied below, doubles address how an ill life is often one “marked not by progress but by recurrence, repetition, and ellipses” (41), as comic critic Jared Gardner claims in relation to his own chronic illness.
Keywords: Double Embodiment; Pictorial Embodiment; Graphic Illness Narratives; Time; Autobiographical Comics.